ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE PERIODE 2017-2021 - Jufri, Achmad; Millah Atmim Lana; Naurah Farah Salsabila; Sabrina Nur Afifah; Darmawan (Jurnal Ekonomi dan Kewirausahaan Kreatif, 2023)
The purpose of this study is to determine the financial performance of PT. Plaza Indonesia Realty Tbk, PT. Roda Vivatex Tbk, and PT Urban Jakarta Propertindo Tbk from 2017 to 2021 using liquidity, solvency, activity and profitability ratios. This study uses secondary data obtained from the company's annual financial reports at IDN financials and on the company's website itself. This study uses a quantitative descriptive method. The results of this study indicate that the company's liquidity when viewed from the current ratio and quick ratio is running quite well, but the cash ratio is not running well, which means the company is less current in its short-term obligations. Then in terms of company solvency, seen from the Debt Asset to Ratio, all companies are in a fairly good category and the Debt to Equity Ratio is only PT Plaza Indonesia Realty Tbk, which is not good, this shows that the company is increasingly finding it difficult to pay long-term obligations. Then, in the company's activities, it can be seen from the inventory turnover of PT Urban Jakarta Propertindo, which is not going well and the asset turnover ratio of the three companies is also not doing well, which means that the company gets less income per dollar of assets. While seen from the profitability using the net profit margin ratio only PT. Urban Jakarta Propertindo Tbk which is above the industry standard so that it shows the company is running quite well in terms of net profit after tax so that the company is able to reduce its operational costs in certain periods while the Return on Assets and Return on Equity ratios of the three companies are below standard industry so that it shows the size of a company is not good for the profitability of the company itself which shows the effectiveness of management in using assets to earn income every year.